Prognostic Value and Outcome for ETV6/RUNX1-Positive Pediatric Acute Lymphoblastic Leukemia: A Report From the South China Children’s Leukemia Group - Qiu, Kun-yin; Xu, Hong-gui; Luo, Xue-qun; Mai, Hui-rong; Liao, Ning; Yang, Li-hua; Zheng, Min-cui; Wan, Wu-qing; Wu, Xue-dong; Liu, Ri-yang; Chen, Qi-wen; Chen, Hui-qin; et al. (Frontiers in Oncology, 2021)
Purpose:To analyzed the outcome of ETV6/RUNX1-positive pediatric acute B lymphoblastic leukemia (B-ALL) with the aim of identifying prognostic value. Method: A total of 2,530 pediatric patients who were diagnosed with B-ALL were classified into two groups based on the ETV6/RUNX1 status by using a retrospective cohort study method from 28 February, 2008 to 30 June, 2020 at 22 participating ALL centers. Results:461(18.2%) cases were ETV6/RUNX1-positive. The proportion of patients with risk factors (age<1 year or ≥10 years, WB≥50×109/L) in ETV6/RUNX1-positive group was significantly lower than that in negative group (P<0.001), while the proportion of patients with good early response (good response to prednisone, D15 MRD < 0.1%, and D33 MRD < 0.01%) in ETV6/RUNX1-positive group was higher than that in negative group (P<0.001, 0.788 and 0.004, respectively). Multivariate analysis of 2,530 patients found that age <1 or ≥10 years, SCCLG-ALL-2016 protocol and MLL were independent predictor of outcome but not ETV6/RUNX1. The EFS and OS of the ETV6/RUNX1-positive group were significantly higher than those of the negative group（3-year EFS：90.11 ± 4.21% vs 82 ± 2.36%，P＜0.0001；3-year OS：91.99 ± 3.92% vs 88.79 ± 1.87%，P＝0.017）. Subgroup analysis showed that chemotherapy protocol, age, prednisone response and D15 MRD were important factors affecting the prognosis of ETV6/RUNX1-positive children. Conclusions: ETV6/RUNX1-positive pediatric ALL show an excellent outcome but lack of independent prognostic significance in South China. However, for older patients who have the ETV6/RUNX1 fusion and slow response to therapy to opt for more intensive treatment.